N-(2,3-Dimethylphenyl)-2,2,2-trimethylacetamide - Gowda, B. Thimme (International Union of Crystallography, 2009)
The N—H bond in the title compound, C(13)H(19)NO, is anti to the C=O bond and is also anti to both the 2- and 3-methyl substituents in the aromatic ring. In the crystal, intermolecular N—H⋯O hydrogen bonds link the molecules into chains propagating along the c axis.